María Teresa Miras Portugal: a pioneer in the study of purinoceptors in chromaffin cells - Artalejo, Antonio R.; Arribas-Blázquez, Marina; Barahona, María Victoria; Llorente-Sáez, Celia; Olivos-Oré, Luis Alcides (Purinergic signalling, 2024)
María Teresa Miras Portugal devoted most of her scientific life to the study of purinergic signalling. In an important part of her work, she used a model system: the chromaffin cells of the adrenal medulla. It was in these cells that she identified diadenosine polyphosphates, from which she proceeded to the study of adrenomedullary purinome: nucleotide synthesis and degradation, adenosine transport, nucleotide uptake into chromaffin granules, exocytotic release of nucleotides and autocrine regulation of chromaffin cell function via purinoceptors. This short review will focus on the current state of knowledge of the purinoceptors of adrenal chromaffin cells, a subject to which María Teresa made seminal contributions and which she continued to study until the end of her scientific life.